Tayma, Saudi-Arabien: Multidisziplinäre Forschungen in der Oase - Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2023)
Multidisciplinary research at the oasis of Tayma, Northwest Arabia, revealed further information on the beginning of oasis cultivation towards the end of the 5th millennium BC and subsequently on the establishment of a substantial 3rd millennium BC occupation also at the centre of the site. Tayma was a significant place at that time with far reaching contacts to urban centres in neighbouring regions. On the long run, these relations laid the foundation for the oasis’ importance in the context of the 1st millennium BC overland caravan trade. Further investigations focused on 2nd and 1st millennium BC contexts of public and residential architecture at the site. The hydrological project continued its work on the reconstruction of the pertaining resource management. First epigraphic investigations in the hinterland of the oasis were also carried out.